2018
DOI: 10.3390/fermentation4030077
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Saccharomyces bayanus CN1 for Fermenting Partially Dehydrated Grapes Grown in Cool Climate Winemaking Regions

Abstract: This project aims to characterize and define an autochthonous yeast, Saccharomyces bayanus CN1, for wine production from partially dehydrated grapes. The yeast was identified via PCR and Basic Local Alignment Search Tool (BLAST) analysis as Saccharomyces bayanus, and then subsequently used in fermentations using partially dehydrated or control grapes. Wine grapes were dried to 28.0°Brix from the control grapes at a regular harvest of 23.0°Brix. Both the partially dehydrated and control grapes were then vinifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…Two yeast strains were used in this study for wine fermentations: the commercial yeast S. cerevisiae strain EC1118 was supplied by Lallemand Inc. (Montreal, Canada) and CN1, which was isolated at CCOVI (St. Catharines, Canada) from the bloom of local Riesling Icewine grapes (Kelly et al, 2018). CN1 was reclassified as an S. uvarum strain, formerly referenced as S. bayanus.…”
Section: Yeast Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two yeast strains were used in this study for wine fermentations: the commercial yeast S. cerevisiae strain EC1118 was supplied by Lallemand Inc. (Montreal, Canada) and CN1, which was isolated at CCOVI (St. Catharines, Canada) from the bloom of local Riesling Icewine grapes (Kelly et al, 2018). CN1 was reclassified as an S. uvarum strain, formerly referenced as S. bayanus.…”
Section: Yeast Strainsmentioning
confidence: 99%
“…The yeast culture build-up and acclimatization procedure was as described in Kelly et al (2018) with the following modifications. Yeast cultures of EC1118 and CN1 were prepared by inoculating plated yeast colonies into 0.48 L of sterile-filtered Cabernet franc or Pinot noir must diluted to 10 °Brix and grown to 2 × 10 8 cell/mL.…”
Section: Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, fermentation is carried out by monoculture of yeast, which provides consistency in the aroma profile and relatively high content of ethyl alcohol. However, to obtain characteristic flavours, increased concentration of desirable esters, and added aroma complexity, winemakers turn to non-Saccharomyces species [4] or strains that belong to the Saccharomyces genus other than S. cerevisiae [5]. It must be highlighted that there are several commercially available strains that belong to both these groups [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they may be tools to avoid stuck fermentations under nitrogen limitations. Accordingly, Kelly et al [7] demonstrated the potential of adapted autochthonous yeasts such as strains of S. bayanus to produce individual wines even in cool climate regions.…”
mentioning
confidence: 99%